Cost comparison of three kinds of compression therapy in venous ulcer - Bruno Emmanuel de Medeiros Pereira; Alana Tamar Oliveira de Sousa; Jael Rúbia Figueiredo de Sá França; Maria Júlia Guimarães Oliveira Soares (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Evolution and cost of three types of compression therapy (single layer, multilayer and Unna boot) in patients with venous ulceration were compared. The evaluation lasted two months and used photographic records and instrument based on pressure ulcer scale for healing (PUSH). Treatment with monolayer compression therapy presented the lowest cost and more efficacy of the three types, with 82% savings compared with the multilayer therapy.